Pemetaan Potensi Destinasi Wisata Di Desa Dongko Kabupaten Trenggalek - Verda Raseindriyasari Bidjaksono; Wahyu Buana Putra; Mohamad Febri Ashiddiqi; Sri Maharani Mardiananingrum TVM (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Dongko Village is one of the villages which is one of the tourist villages in Trenggalek Regency. The development of the potential of a tourism village in Dongko Village has the aim of identifying natural, cultural and man-made potential in the village and can be developed as a tourist attraction and is able to improve the quality of natural resources as well as human resources, explore problems and factors that become weaknesses in developing a tourism village, as well as designing a strategy to develop the tourism village potential of Dongko Village based on existing potentials and problems. We used empirical methods with qualitative descriptive analysis in compiling this research. Obtaining data using this method is because researchers go directly to the research location, namely Dongko Village. Sources of data collected by research methods in the form of observations, interviews, observations, and documentation.